KONSEP FILOSOFIS PROGRAM STUDI PENDIDIKAN BIOLOGI - Nanang Purwanto (LPPM Universitas KH.A.Wahab Hasbullah Jombang, 2015)
Education is a planned and conscious effort to bring about an atmosphere of learning and the learning process so that learners are actively developing potential for her to have a religious, spiritual power of self-control, personality, intelligence, attitudes, and noble, as well as the necessary skills themselves and society. Biology is the study of living organisms, their environment and their lives. So literally, Biology education is an effort to introduce a living being, the environment and life to the learners with the goal of learners can understand, describe, and implement values that are contained in this knowledge for the benefit of self learners and the community. Educators, prospective educators, curriculum developers and observers should understand that education is everything to the needs of learners in the teaching activities, in accordance with the direction of educational objectives. KEYWORDS: philosophical, concepts Biology education